Complex magnetic states of heavy fermion compound CeGe: Магнетизм - Haines, C.R.S.; Marcano, N.; Smith, R.P.; Aviani, I.; Espeso, J.I.; Sal, J.C. Gуmez; Saxena, S.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2012)
The intermetallic compound CeGe exhibits unusual magnetic behavior due to the interplay between the Kondoand the antiferromagnetic coupling. This particular system is interesting because the Kondo temperature is close to the Néel temperature, resulting in a close competition between the low-temperature interactions, which can betuned by means of varying external parameters such as pressure and applied magnetic field. Interestingly, magnetization measurements up to 12 kbar reveal that the Néel temperature is not affected by pressure. Measurements of the electrical resistivity, however, show that the sharp upturn appearing below TN is sensitive to pressures up to 15 kbar. This suggests that pressure may change the complex antiferromagnetic spin structure. The validity of an explanation based on the magnetic superzones seen in the rare earths is discussed here.